Packaging Design For Educational Toys Bornea Toys With Mega-Pack & Well-Organized Concept - Mardiana, Christin; Pahlevy, Trianata (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
A packaging is a silent salesman that determines whether consumers decide to buy the product or not. Consumers can see, feel, touch, recognize, and pay attention to good quality toy packaging. Borneo Toys is a product that serves children, in that reason, the researchers designed the packaging in which becomes a storage, protective, and product interaction media with consumers. In phase of design method, researcher used: collecting theoretical foundations, formulating design requirements, making mood reference boards, designing packaging frameworks, packaging graphics, and prototypes. The final result is a prototype of the packaging design of the Borneo Toys toy, with a concept of 'Mega Pack Well-Organized', meaning that in one packaging can store 10 different models of animal toys. The novelty of this design lies in the configuration of the storage layout of the toy pieces, where the layout arranged by type of shape so as to present a new experience of storing toys for children, because they have to guess the position and arrangement of these pieces like a puzzle game. There is a manual book in this package that can make it easier for children to play Borneo Toys.